Looking back, moving forward : tranformation and ethical practice in the Ghanaian Church of Pentecost - Daswani, Girish (Toronto : University of Toronto Press, 2015)
Looking Back, Moving Forward investigates the embodied practices, interpersonal relationships, and moments of self-reflection in the lives of members of the Church of Pentecost in Ghana and amongst the Ghanaian diaspora in London.
Introduction -- Rupture and continuity -- Uncertainties and dilemmas -- Prophets and prayer -- Individuality and dividuality -- Kinship and migration -- African Christians in London -- Citizens of heaven -- Epilogue.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Church of Pentecost; Church of Pentecost -- Membership; Church of Pentecost; Pentecostal converts -- Ghana; Pentecostal converts -- England -- London; Religion and ethics; RELIGION -- Christianity -- Denominations; Membership requirements; Pentecostal converts; Religion and ethics; England -- London; Ghana; RELIGION / General; Electronic books